Invasive grasses change landscape structure and fire behaviour in Hawaii. Issue 4 (26th May 2014) - Ellsworth, Lisa M.; Litton, Creighton M.; Dale, Alexander P.; Miura, Tomoaki; Pausas, Juli
Abstract Questions How does potential fire behaviour differ in grass‐invaded non‐native forests vs open grasslands? How has land cover changed from 1950–2011 along two grassland/forest ecotones in Hawaii with repeated fires? Location Non‐native forest with invasive grass understory and invasive grassland (Megathyrsus maximus) ecosystems on Oahu, Hawaii, USA. Methods We quantified fuel load and moisture in non‐native forest and grassland (Megathyrsus maximus) plots (n = 6) at Makua Military Reservation and Schofield Barracks, and used these field data to model potential fire behaviour using the BehavePlus fire modelling program. Actual rate and extent of land‐cover change were quantified for both areas from 1950–2011 with historical aerial imagery. Results Live and dead fuel moisture content and fine fuel loads did not differ between forests and grasslands. However, mean surface fuel height was 31% lower in forests (72 cm) than grasslands (105 cm; P < 0.02), which drove large differences in predicted fire behaviour. Rates of fire spread were 3–5 times higher in grasslands (5.0–36.3 m·min−1) than forests (0–10.5 m·min−1; P < 0.001), and flame lengths were 2–3 times higher in grasslands (2.8–10.0 m) than forests (0–4.3 m; P < 0.01). Between 1950 and 2011, invasive grassland cover increased at both Makua (320 ha) and Schofield (745 ha) at rates of 2.62 and 1.83 ha·yr−1, respectively, with more rapid rates of conversion before active fire management practices were implemented in the early 1990s. Conclusions These results support accepted paradigms for the tropics, and demonstrate that type conversion associated with non‐native grass invasion and subsequent fire has occurred on landscape scales in Hawaii. Once forests are converted to grassland there is a significant increase in fire intensity, which likely provides the positive feedback to continued grassland dominance in the absence of active fire management.